2022
DOI: 10.1136/bmjopen-2021-056140
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus self-sampling for cervical cancer screening among women in sub-Saharan Africa: a scoping review protocol

Abstract: IntroductionEvidence shows that women in sub-Saharan Africa have high rates of cervical cancer (CC) mortality compared with women in high-income countries. Effective screening programmes have significantly reduced the burden of CC in high-income countries. Self-sampling for human papillomavirus testing (HPVSS) has been reported to increase the participation and engagement of women in CC screening. Before HPVSS can be introduced for CC screening there is a need to establish its acceptability among end-users to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A systematic scoping review protocol was published in BMJ Open journal under the title: Human papillomavirus self-sampling for cervical cancer screening among women in sub-Saharan Africa: a scoping review protocol. 12 This scoping review was conducted according to the methodological framework proposed by Arksey and O’Malley 13 and Levac et al . 14 According to Arksey and O’Malley’s framework, a scoping review follows five stages: (1) identify the research question; (2) identify relevant studies; (3) select eligible studies; (4) charting the data; (5) collating, summarising and reporting the results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic scoping review protocol was published in BMJ Open journal under the title: Human papillomavirus self-sampling for cervical cancer screening among women in sub-Saharan Africa: a scoping review protocol. 12 This scoping review was conducted according to the methodological framework proposed by Arksey and O’Malley 13 and Levac et al . 14 According to Arksey and O’Malley’s framework, a scoping review follows five stages: (1) identify the research question; (2) identify relevant studies; (3) select eligible studies; (4) charting the data; (5) collating, summarising and reporting the results.…”
Section: Methodsmentioning
confidence: 99%
“…The published methodology was made available on 19 September 2021, and it can be accessed online (https://osf.io/ba8fc. A systematic scoping review protocol was published in BMJ Open journal under the title: Human papillomavirus self-sampling for cervical cancer screening among women in sub-Saharan Africa: a scoping review protocol 12. This scoping review was conducted according to the methodological framework proposed by Arksey and O’Malley13 and Levac et al 14.…”
Section: Methodsmentioning
confidence: 99%
“…This systematic review builds on the findings of a scoping review conducted to establish the acceptability of HPV self-sampling for screening cervical cancer in SSA. The scoping review was published elsewhere [ 15 ]. A systematic search to identify literature on the acceptability of self-sampling for HPV testing was undertaken across 5 major electronic databases and a grey literature search.…”
Section: Methodsmentioning
confidence: 99%
“…A systematic search to identify literature on the acceptability of self-sampling for HPV testing was undertaken across 5 major electronic databases and a grey literature search. This systematic review followed the same search strategy [ 15 ] and considered qualitative and mixed methods studies that showed evidence of the experiences and perspectives of women, health workers and policymakers regarding self-sampling for HPV-based cervical cancer screening. Studies were included if they employed qualitative research designs such as focus groups, in-depth interviews and semi-structured interviews.…”
Section: Methodsmentioning
confidence: 99%